The Effect of Plant Density on the Yield of Sunflower Hybrids in 2000-2002 - Szabó, András; Pepó, Péter (Acta Agraria Debreceniensis, 2004)
In order to ensure modern Hungarian sunflower production, the development of hybrid-specific techniques are highly important. The continual expansion in hybrid choice makes the examination of genotypes necessary in the relation of genotype and environment interactions and critical factors. The Plant density as a complex determinant factor has a strong effect on sunflower yield, quality and plant hygiene. As a result of the experiments, we can state that the optimal density was 45.000-65.000 plant/hectar. In 2001-2002, the optimal density was 45.000-55.000 plant/hectar; while in 2000, it was 65.000 plant/hectar.